The role and characteristics of images in language and culture teaching - Djermouni, Rekia (The International tax journal, 2026)
This research paper examines the role of educational images in language and culture teaching by analyzing their concept, characteristics, and pedagogical functions, in addition to their various types and the role of modern technology in enhancing their presence within the educational process. The study shows that educational images represent an effective didactic tool that contributes to simplifying abstract concepts, bringing meanings closer, and enhancing learners’ linguistic achievement by strengthening memory and developing lexical repertoire. The results also highlight the important role of images in fostering imagination and creativity, stimulating linguistic expression, and their ability to increase learning motivation and overcome individual differences among learners, making them more interactive and engaged in knowledge construction. The study further confirms that the integration of images and text, along with the use of digital media, contributes to improving comprehension and developing communicative competence, giving learning a more realistic and effective dimension. The study concludes that educational images have become a fundamental component of modern education, requiring systematic and well-planned use to achieve effective learning based on interaction and the development of linguistic and cultural competencies among learners.